Analisis Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan pada Counter Handhphone â€œVenus Cellularâ€ Tangerang - Risfa Dewi; Andri Suseno; Mertha Widiyastuti Adhi (Ridwan Institute, 2021)
The purpose of this study was to analyze the Effect of Product Quality on Customer Satisfaction on Handhphone Counter